Factors influencing wider acceptance of Computer Assisted Orthopaedic Surgery (CAOS) technologies for Total Joint Arthroplasty - Craven, Michael P.; Davey, Shirley M.; Martin, Jennifer L. (Multidisciplinary Assessment of Technology Centre for Healthcare (MATCH), 2005)
Computer-assisted orthopaedic surgery (CAOS) promises to improve outcomes of joint arthroplasty through better alignment and orientation of implants, but take up has so far been modest. Following an overview of CAOS technologies covering image-guided surgery, image-free and robotic systems, several factors for lack of penetration are identified. These include poor validation of accuracy, lack of standardisation, inappropriate clinical outcomes measures for assessing and comparing technologies, unresolved debate about the effectiveness of minimally invasive surgery, and issues of medical device regulations, cost, autonomy of surgeons to choose equipment, ergonomics and training. The paper concludes that dialogue between surgeons and manufacturers is needed to develop standardised measurements and outcomes scoring systems that are more appropriate for technology comparisons, and encourages an increased awareness of user requirements.